Humidification Solution as a Source for Spreading Burkholderia cepacia in a Neonatal Intensive Care Unit - Baysal, Bora (Journal of Pediatric Infectious Diseases, 2020)
Burkholderia cepacia is an important opportunistic organism in hospitalized and immunocompromised patients especially in newborns. The natural ecology of these bacteria associated with plants is also a cause of infectious potential. The disease-causing potential of bacteria as a nosocomial pathogen may be due to its ability to survive in antiseptic solutions, contamination equipment. The patient was hospitalized for prematurity and respiratory distress syndrome. He was treated with surfactant intratracheally for the respiratory distress syndrome. Umbilical catheter was inserted. Ampicillin and gentamicin treatments were initiated. The patient who received respiratory support for a long time was given a steroid protocol because of bronchopulmonary dysplasia. Burkholderia cepacia was detected in the blood and tracheal aspirate cultures of the patient, whose infection markers increased and a new area of infection was detected on the chest radiograph. Colistin and ciprofloxacin treatments were given according to the culture antibiogram. Screening tests revealed B. cepacia colonization in incubator moistening solutions. All incubator humidification solutions in the hospital were changed. Burkholderia cepacia is a rare cause of nosocomial infection in intensive care units but resistant to many treatments. With its capability to colonize water and grow on microbicides, the presence of B. cepacia in a patient's blood warrants further investigation in institutions providing care.
Keywords: Burkholderia cepacia; neonatology; prematurity; humidification solution